Tissue-Specific Distribution of Legacy and Emerging Organophosphorus Flame Retardants and Plasticizers in Frogs - Yin-E Liu; Xiao-Jun Luo; Ke-Lan Guan; Chen-Chen Huang; Xue-Meng Qi; Yan-Hong Zeng; Bi-Xian Mai (Toxics, 2021)
Five types of tissues, including the liver, kidney, intestine, lung, and heart, were collected from black-spotted frogs and bullfrogs to study the tissue-specific accumulation of organophosphorus flame retardants (PFRs) and plasticizers. Thirteen PFRs and nine plasticizers were detected, with average total concentrations of 1.4–13 ng/g ww and 858–5503 ng/g ww in black-spotted frogs, 3.6–46 ng/g ww and 355–3504 ng/g ww in bullfrogs. Significant differences in pollutant concentrations among different tissues in the two frog species were found, indicating the specific selectivity distribution of PFRs and plasticizers. Overall, liver tissues exhibited significantly higher pollutant concentrations. The pollutant concentration ratios of other tissue to the sum of liver tissue and other tissues (OLR, Cother/(Cother + Cliver)) corresponding to male frogs were significantly greater than those of females, suggesting that male frogs could have higher metabolic potentials for PFRs and plasticizers. No obvious correlations between OLR and log KOW were found, indicating that the other factors (e.g., bioaccumulation pathway and metabolism) besides lipophicity could influence the deposition of PFRs and plasticizers in frog livers. Different parental transfer patterns for PFRs and plasticizers were observed in frogs when using different tissues as parental tissues. Moreover, the liver tissues had similar parental transfer mechanism with muscle tissues.